2017
DOI: 10.1108/jaar-04-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Relations between usage patterns of performance indicators and the role of individual firms in fresh fruit agri-food supply chains

Abstract: This paper reports the use of performance metrics among 121 Brazilian agribusiness companies, with the aim of helping accountants and academics to understand the actual use of performance metrics in non-integrated supply chains. Design/methodology/approach To identify which performance metrics are used among supply chain partners, four independent clusters representing specific supply chain roles (input suppliers, farmers, distributors, and retailers) were formed. Data relating to 49 performance metrics was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
0
13
0
5
Order By: Relevance
“…[2] The situation in fresh produce is very similar to the opportunistic and adversarial nature of transactions reported by Bowman et al (2013) in supermarket supply chains for pork and in Free's (2007Free's ( , 2008 investigations into potentially coercive practices related to category management. It also resonates with practices by intermediaries in the fast fashion garment industry (Neu et al, 2014), an industry that is also disintegrated though not to the extent that food supply chains are fragmented and non-integrated (Bowman et al, 2013;Callado and Jack, 2017). The seminal paper exposing the use of accounting and IT by supermarkets to gain power over producers is Frances and Garnsey (1996).…”
Section: Introductionmentioning
confidence: 90%
“…[2] The situation in fresh produce is very similar to the opportunistic and adversarial nature of transactions reported by Bowman et al (2013) in supermarket supply chains for pork and in Free's (2007Free's ( , 2008 investigations into potentially coercive practices related to category management. It also resonates with practices by intermediaries in the fast fashion garment industry (Neu et al, 2014), an industry that is also disintegrated though not to the extent that food supply chains are fragmented and non-integrated (Bowman et al, 2013;Callado and Jack, 2017). The seminal paper exposing the use of accounting and IT by supermarkets to gain power over producers is Frances and Garnsey (1996).…”
Section: Introductionmentioning
confidence: 90%
“…The study contributes to the on-going debate on measuring performance in the agri-food sector (Fattahi et al, 2013;Chopra et al, 2017;Aramyan et al, 2006;Beamon, 1999). Previous studies have confirmed the perceived importance of performance indicators for chain members (Gunasekaran et al, 2004;Montero et al, 2018;Callado and Jack, 2017;Aramyan et al, 2006) to find out whether performance measurement indicators are perceived relevant at the different chain levels of agri-food chains. This study further develops this field of research, adding novel focus on the perceived chain performance contribution of the chain partners to the individual performance.…”
Section: Theoretical Implicationsmentioning
confidence: 76%
“…The Kruskal-Wallis test, an ANOVA equivalent test for k independent samples. The analyses determined whether any significant differences exist when comparing chain partner's performance contribution to individual chain performance (Callado and Jack, 2017;Kühne et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This research focuses on food security and community welfare in all provinces in Sumatera. Data were obtained from the sustainable development goals data in 2015 (Badan Pusat Statistik, 2016), with a total sample of 152 districts/cities located in Sumatera as the unit of analysis. The causal relations between variables (the relationship between availability (X1), accessibility (X2), and absorption (X3) and food security (Y1), and the relationship between food 202 WJSTSD 15,2 security (Y1) and community welfare (Y2)) were examined using covariance-based structural equation modeling using WarpPLS.…”
Section: Methodsmentioning
confidence: 99%